2015
DOI: 10.5539/ijbm.v10n7p208
|View full text |Cite
|
Sign up to set email alerts
|

Succession Decision in Vietnamese Family Companies

Abstract: This study examines the relationship between the choices of family or outside CEO with company performance. The sample of this study covered 65 Vietnamese family companies in 17 industries. The findings indicate, as anticipated, that family CEO enhanced company performance greater than outside CEO. Within the family company, CEO-successor enhanced the firm value lower than the CEO-founder. Contacts with the business environment, education, experience and sufficient business capital may provide young CEOs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Family legitimacy and networks are still too underdeveloped to be a source of highly competitive advantage to be exploited by family CEOs. On the other hand, FFs may be too busy to prepare for their first succession (Viet, 2015) in which exiting family CEOs need to prepare the business for their descendants, while young family leaders learn to accumulate experience. Additionally, although family CEOs may have political connections through participating in politics, connected family CEOs are new and may be inexperienced in a fierce political arena in transition economies.…”
Section: Discussionmentioning
confidence: 99%
“…Family legitimacy and networks are still too underdeveloped to be a source of highly competitive advantage to be exploited by family CEOs. On the other hand, FFs may be too busy to prepare for their first succession (Viet, 2015) in which exiting family CEOs need to prepare the business for their descendants, while young family leaders learn to accumulate experience. Additionally, although family CEOs may have political connections through participating in politics, connected family CEOs are new and may be inexperienced in a fierce political arena in transition economies.…”
Section: Discussionmentioning
confidence: 99%
“…Involving children early in family businesses enhance the chances of attaining a smooth descent process (Goldberg, 1996;Haag, Helin and Melin, 2006). Further, in a contemplation where 65 house-owned assembly in 17 separate industries was deportment to find out if family CEOs amended the organisation's bottom line greater than outside CEOs, the results showed that family members that were successors in a company enhanced the organisation's appreciate more than successors that were not lineage members (Viet, 2015). It is critical to tone that the key motivator for family-run firms across the ball is the need to keep the calling in the patronymic hence, entwine lineage members in the running of the business is an imperative.…”
Section: Involvement Of Family Membersmentioning
confidence: 99%